2020
DOI: 10.1177/2158244019900184
|View full text |Cite
|
Sign up to set email alerts
|

When Servant Leaders Inspire Followers to Become Organizational Citizens? Empirical Evidence From Vietnam

Abstract: The purpose of this article is to contribute to the existing servant leadership literature, especially at the individual level of analysis in new settings, by examining the potential joint effects of servant leadership, dyadic duration, and job self-efficacy, with organizational citizenship behaviors (OCBs) as the dependent variable. We, after analyzing survey data from 148 leader–follower dyads collected from an engineering venture, find that dyadic duration is a significant moderator of the relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 65 publications
0
18
0
1
Order By: Relevance
“…There is much emphasis on transcending one's self-interest towards followers' interest (Sendjaya et al, 2008;Graham, 1991) through creating a ubiquitous social context which will have a positive effect on employee's attitude (Walumbwa et al, 2010). Servant leaders want the followers to be organizational citizens (Thao and Kang, 2020) through which they can foster followers' OCB (Elche et al, 2020;Newman et al, 2017;Stone et al,2004;Russell, 2001;Podsakoff et al, 2000;Greenleaf, 1997;Smith et al,1983).…”
Section: Servant Leadership and Followers' Organizational Citizenship Behaviourmentioning
confidence: 99%
“…There is much emphasis on transcending one's self-interest towards followers' interest (Sendjaya et al, 2008;Graham, 1991) through creating a ubiquitous social context which will have a positive effect on employee's attitude (Walumbwa et al, 2010). Servant leaders want the followers to be organizational citizens (Thao and Kang, 2020) through which they can foster followers' OCB (Elche et al, 2020;Newman et al, 2017;Stone et al,2004;Russell, 2001;Podsakoff et al, 2000;Greenleaf, 1997;Smith et al,1983).…”
Section: Servant Leadership and Followers' Organizational Citizenship Behaviourmentioning
confidence: 99%
“…He bases this conclusion upon values such as those that Hofstede [16] and House et al [17] identified in global leadership and OCB effectiveness. More recently, Thao and Kang [18] indirectly investigated the moderating effect of self-efficacy in SL on OCB through the dyadic interaction of leader and follower. On the basis of previous studies, it is proposed that an employee's self-efficacy is an important psychological mechanism determining the relationship between SL and OCB.…”
Section: Introductionmentioning
confidence: 99%
“…In a narrower sense, the notion of serving in SL refers primarily to serving the leader's subordinates (cf. Hunter et al, 2013;Thao and Kang, 2020). Thao and Kang (2020, p. 2) write that servant leaders are "known for their unconditional support of their followers, listening to followers' needs and interests, providing opportunities for followers to take the initiative, participating in the decision-making process, demonstrating an ethical presence, and encouraging followers to contribute to society.…”
Section: Ethics and The Servant Leadership Philosophymentioning
confidence: 99%